Ruminal metabolism of grass silage soluble nitrogen fractions - Ahvenjärvi, Seppo; Vaga, M.; Vanhatalo, Aila; Huhtanen, P. (American Dairy Science Association, 2018)
The present study was conducted to investigate ruminal N metabolism in dairy cows using 15N-labeled N sources and dynamic models. The data summarized in this study were obtained from 2 of 4 treatments whose effects were determined in a 4 × 4 Latin square design. Soluble N (SN) isolated from timothy grass silage labeled with 15N and ammonia N (AN) labeled with 15N were administered into the rumen contents of 4 ruminally cannulated dairy cows. Ruminal N pool sizes were determined by manual evacuation of rumen contents. The excess 15N-atom% was determined in N-fractions of rumen digesta grab samples that were collected frequently between 0 to 72 h and used to determine 15N metabolism in the rumen. Calculations of area under the curve ratios of 15N were used to estimate proportions of N fractions originating from precursor N pools. A model including soluble nonammonia N (SNAN), AN, bacterial N, and protozoal N pools was developed to predict observed values of 15N atomic excess pool sizes. The model described the pool sizes accurately based on small residuals between observed and predicted values. An immediate increase in 15N enrichment of protozoal N suggests physical attachment of bacteria pool to protozoa pool. The mean proportions of bacterial N, protozoal N, and feed N in rumen solid phase were 0.59, 0.20, and 0.21, respectively. These observations suggest that protozoal N accounted for 0.25 of rumen microbial N. About 0.90 of the initial dose of AN was absorbed or taken up by microbes within 2 h. Faster 15N enrichment of bacterial N with SN than with AN treatment indicates a rapid adsorption of SNAN to microbial cells. Additionally, the recovery of 15N as microbial and feed N flow from the rumen was approximately 0.36 greater for SN than for the AN treatment, indicating that SNAN was more efficiently used for microbial growth than AN. The present study indicated that about 0.15 of microbial N flowing to the duodenum was of protozoal origin and that 0.95 of the protozoal N originated from engulfed bacterial N. The kinetic variables indicated that 0.125 of SNAN escaped ruminal degradation, which calls into question the use of in situ estimations of protein degradation to predict the flow of rumen undegradable protein.
Keywords: modeling; bacterial nitrogen; ammonia nitrogen; dairy cows; nitrogen